Periodontal regeneration after third molar extraction causing attachment loss in distal and furcation sites of the second molar: a case report with 12 months follow-up - Monteiro, Rafael Jordão Storino Vaz (2022)
Introduction: The periodontal support apparatus is extremely important due to guarantee insertion to the tooth. It helps with the maintenance of the structural resistance and reconstructive property, and its loss may contribute to root exposure and the possibility to obtain an augmentation of the sensitivity. Thereby, this paper aimed to describe a case report, using regenerative techniques in a bone loss involving distal and furcation regions of the mandibular second molar, which was associated with the extraction of the adjacent impacted third molar without bone interposing. Case presentation: The patient was referred to a private dental clinic reporting an unpleasant odor while using dental floss in the distal region of the mandibular left second molar, during the three years. In addition, reported a history of extraction of the wisdom tooth six years ago. Periapical examination and periodontal index were performed and an extensive radiolucent image involving distal and furcation regions, with a 12 mm probing depth involving the distal root at tooth (2nd molar). No other region showed probing depth greater than 3mm. Thus, after rigorous scaling and root planing, periodontal guided tissue regeneration was performed as an attempt to fill the bone defect. Conclusion: The regenerative process is a predictable way to treat vital mandibular second molar after extraction of the adjacent third molar. Clinicians must give special attention to extraction involving the mandibular third molars, mainly when there is no bone interposed between the second and third molars.